Evaluation of the Anatomic Position of the Mandibular Canal Regarding to the Segments of the Mandibular Sagittal Split Ramus Osteotomy to Diminish the Possibility of Injuries: a Pilot Study - Victor Diniz Borborema dos Santos; Salomão Israel Monteiro Lourenço Queiroz; Alessandro Costa da Silva; Susana Silva; José Sandro Pereira da Silva; Gustavo Vicentis de Oliveira Fernandes; Adriano Rocha Germano (Stilus Optimus, 2022)
Objectives: This pilot study evaluated the relationship between inferior alveolar nerve location through computed tomography scan and intraoperative inferior alveolar nerve entrapment after bilateral sagittal split osteotomy. Material and Methods: Overall, 20 helicoidal computed tomography scans were evaluated in patients with facial deformities who underwent to bilateral sagittal split osteotomy (BSSO). The distance from the mandibular canal to the internal surface of the buccal and lingual cortical bone, mandibular thickness, bone density and proportion of medullary and cortical bone in 3 regions were evaluated. During the intraoperative period, the segment to which the nerve remained adhered after performing BSSO was analysed, and the data correlated. Results: The distance from the mandibular canal to the buccal cortical bone showed a mean of 2.6 mm when the inferior alveolar nerve was adhered to the distal segment and mean of 0.7 mm when the nerve was adhered to the proximal segment. The thickness was 11.2 mm and 9.8 mm when the nerve was adhered the distal the proximal segments respectively. Mandibular thickness, distance from the mandibular canal to the buccal and lingual cortical were statistically related to intraoperative nerve entrapment (P < 0.05). Conclusions: Narrow jaws and the distance from the mandibular canal to buccal cortical bone less than 2 mm increases the risk of the inferior alveolar nerve entrapment in bilateral sagittal split osteotomy.